Minding animals in the Old and New Worlds : a cognitive historical analysis - Wagschal, Steven, 1967- (Toronto Iberic, 2018)
Relying on current research in cognitive science and the philosophy of animal cognition, Minding Animals in the Old and New Worlds explores how humans have understood non-human animals in the Iberian world, from the Middle Ages through the Early Modern period.